Case of invasive nontypable Haemophilus influenzae respiratory tract infection with a large quantity of neutrophil extracellular traps in sputum - Hamaguchi S; Seki M; Yamamoto N; Hirose T; Matsumoto N; Irisawa T; Takegawa R; Shimazu T; Tomono K (Dove Medical Press, 2012)
Shigeto Hamaguchi,1,* Masafumi Seki,1,* Norihisa Yamamoto,1 Tomoya Hirose,2 Naoya Matsumoto,2 Taro Irisawa,2 Ryosuke Takegawa,2 Takeshi Shimazu,2 Kazunori Tomono11Division of Infection Control and Prevention, 2Department of Traumatology and Acute Critical Medicine, Osaka University Graduate School of Medicine, Osaka, Japan *These authors contributed equally to this workAbstract: Haemophilus influenzae type b was once the most common cause of invasive H. influenzae infection, but the incidence of this disease has decreased markedly with introduction of conjugate vaccines to prevent the disease. In contrast, the incidence of invasive infection caused by nontypable H. influenzae has increased in the US and in European countries. Neutrophil extracellular traps (NETs) are fibrous structures released extracellularly from activated neutrophils during inflammation, including in pneumonia, and rapidly trap and kill pathogens as a first line of immunological defense. However, their function and pathological role have not been fully investigated. Here, we report a case of fatal nontypable H. influenzae infection with severe pneumonia and bacteremia in an adult found to have a vast amount of NETs in his sputum. The patient had a two-day history of common cold-like symptoms and was taken to the emergency room as a cardiopulmonary arrest. He recovered temporarily, but died soon afterwards, although appropriate antibiotic therapy and general management had been instituted. Massive lobular pneumonia and sepsis due to nontypable H. influenzae was found, in spite of H. influenzae type b vaccine being available. His sputum showed numerous bacteria phagocytosed by neutrophils, and immunohistological staining indicated a number of NETs containing DNA, histone H3, and neutrophil elastase. This case highlights an association between formation of NETs and severe respiratory and septic infection. An increase in severe nontypable H. influenzae disease can be expected as a result of “athogen shift”due to increased use of the H. influenzae type b vaccine in Japan.Keywords: neutrophil extracellular traps, sepsis, pneumonia, Haemophilus influenzae, type b, nontypable